DESIGN OF A CATTLE RECORDING APPLICATION USING THE DESIGN THINKING METHOD - Hardinata, Rio Septian; Wijaya, Rian Farta; Putra, Andhika; Nastari, Laila (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
Increasing livestock production is inseparable from the use of technology in farming. One of the technologies that can help breeders increase their production is to have good livestock data records, the Karya Bersama farmer group realizes that the use of technology in the livestock sector is urgently needed, namely livestock recording, livestock recording can help breeders store or record livestock properly, by using the design thinking method, researchers can find out the application of recording sheep livestock needed by breeders, especially farmer groups working together.